Conference on Lasers and Electro-Optics 2019
DOI: 10.1364/cleo_qels.2019.fth1b.2
|View full text |Cite
|
Sign up to set email alerts
|

Subcycle observation of terahertz-driven minimally dissipative spin switching

Abstract: Article 25fa pilot End User AgreementThis publication is distributed under the terms of Article 25fa of the Dutch Copyright Act (Auteurswet) with explicit consent by the author. Dutch law entitles the maker of a short scientific work funded either wholly or partially by Dutch public funds to make that work publicly available for no consideration following a reasonable period of time after the work was first published, provided that clear reference is made to the source of the first publication of the work.This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Nowadays though, enough solutions exist so that the interest on the use of THz has raised in many fields. Notably, the field of spintronics, conventionally limited to the sub-GHz, GHz and optical regimes for a long time, is now overtaken by THz studies where unexpected dynamics [1][2][3][4][5] and resonant modes have been observed [6][7][8] . Some of these works, particularly when dealing with magnetization manipulation, require high fluence THz pulses, preferably of unipolar character.…”
Section: Calibration Of Terahertz Sampling Detectors For Intense Unip...mentioning
confidence: 99%
“…Nowadays though, enough solutions exist so that the interest on the use of THz has raised in many fields. Notably, the field of spintronics, conventionally limited to the sub-GHz, GHz and optical regimes for a long time, is now overtaken by THz studies where unexpected dynamics [1][2][3][4][5] and resonant modes have been observed [6][7][8] . Some of these works, particularly when dealing with magnetization manipulation, require high fluence THz pulses, preferably of unipolar character.…”
Section: Calibration Of Terahertz Sampling Detectors For Intense Unip...mentioning
confidence: 99%
“…14 Finally, (iii) robust retention of information is guaranteed because of the negligible impact of high magnetic fields up to 60 T. 15,16 The last feature also poses a challenge because very strong magnetic fields may be required to switch the AFM order 17 . However, recent theoretical 18 and experimental works paved the way to the manipulation of the AFM order 19 by electrical currents in inversion-asymmetric AFM materials such as CuMnAs 20,21,22,23 and Mn2Au 24,25 . Charge-current pulses were shown to reproducibly switch CuMnAs devices (such as in Fig.…”
Section: Introductionmentioning
confidence: 99%